Methoxycarbonylation of Styrene Using a New Type of Palladium Complexes Bearing P,N-Donor Ligands as Catalysts - Moya-Duran, S; Moya-Duran, S; Brown-Alvarez, K; Brown-Alvarez, K (Kluwer Academic Publishers, 2015)
Palladium complexes of the type [Pd(L)Cl(PPh3)]Cl (L = 2-diphenylphosphinoamino)pyrimidine, or 2-diphenylphosphinoaniline), generated in situ by addition of one equivalent of PPh3 to the corresponding neutral complexes [Pd(L)Cl2], were tested as catalysts for the methoxycarbonylation of styrene. The catalyst containing the pyrimidinyl ligand shows almost complete chemo- and regioselectivity together with a high conversion rate. However, in identical conditions, the [Pd(Ph2PNHC6H4PPh2)Cl2] complex, where the P,N-ligand has been replaced by a related bidentate P-donor one, shows a significantly lesser performance. (Chemical Presented). © 2015 Springer Science+Business Media.